Transcriptome analysis provides new insights into the response of canine intestinal epithelial cells treated by sulforaphane: a natural product of cruciferous origin - Kaiqi Li; Jin Yan; Shiqi Wang; Chuyang Zhu; Qi Zhu; Sichen Lu; Ping Hu; Dessie, Tadelle; In Ho Kim; Ahmed, A.A.; Hao-Yu Liu; Ennab, W.; et al. (Frontiers Media, 2024)
This study presents a comprehensive transcriptome analysis of canine intestinal epithelial cells following treatment with sulforaphane (SFN), a naturally occurring compound found in cruciferous vegetables with established anti-inflammatory and antioxidant properties. Through high-throughput sequencing, we identified 29,993 genes, among which 1,612 were differentially expressed, with 792 up-regulated and 820 down-regulated in response to SFN treatment. Our analysis revealed significant enrichment of genes in pathways associated with the inflammatory response, lipid metabolism, oxidative stress response, and T-cell mediated immunity, suggesting SFN’s potential in modulating these biological processes. Notably, the PPARγ gene, which plays a crucial role in the body’s oxidative stress and inflammatory response, was highly up-regulated, indicating its possible centrality in SFN’s effects. Gene–gene interaction analysis further supported SFN’s role in alleviating inflammation through PPARγ, with key genes in oxidat